2022
DOI: 10.1002/adfm.202200660
|View full text |Cite
|
Sign up to set email alerts
|

Field‐Free Magnetization Switching Driven by Spin–Orbit Torque in L10‐FeCrPt Single Layer

Abstract: Electrical switching of magnetization through spin-orbit torque (SOT) induced by a composition gradient in single-layer L1 0 -FePt has garnered considerable research interest owing to its inherent superior perpendicular magnetic anisotropy (PMA) that provides ultrahigh capacity to magnetic storage and memory devices. However, a large in-plane external magnetic field is typically required to assist SOT-driven switching, which is still a limitation for the practical application of L1 0 -FePt. This study reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Recently, experiments have established that a strong bulk-type net damping-like spin-orbit torque (Figure 15a) can be generated within single-crystalline GaMnAs with bulk inversion asymmetry [46] and some thick, strong spin-orbit coupling magnetic single layers, e.g., Co1-xPtx, [52,114,115] Fe1-xPtx, [53,120,121] Fe1-xTbx, [54] Co1-xTbx, [122,152] GdFeCo, [116,153] and L10-FeCrPt. [154] Switching of perpendicular magnetization by such bulk SOTs has been demonstrated. For example, Liu et al [54] reported bulk SOT switching of 20 nm Fe0.42Tb0.58 layer with a giant anisotropic field of 36.8 kOe, high coercivity of 1.72 kOe and moderate magnetization of 134 emu/cm 3 at a low current density of 5.5×10 6 A/cm 2 under an in-plane longitudinal magnetic field of ±3 kOe (Figure 15b).…”
Section: Bulk Sot Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, experiments have established that a strong bulk-type net damping-like spin-orbit torque (Figure 15a) can be generated within single-crystalline GaMnAs with bulk inversion asymmetry [46] and some thick, strong spin-orbit coupling magnetic single layers, e.g., Co1-xPtx, [52,114,115] Fe1-xPtx, [53,120,121] Fe1-xTbx, [54] Co1-xTbx, [122,152] GdFeCo, [116,153] and L10-FeCrPt. [154] Switching of perpendicular magnetization by such bulk SOTs has been demonstrated. For example, Liu et al [54] reported bulk SOT switching of 20 nm Fe0.42Tb0.58 layer with a giant anisotropic field of 36.8 kOe, high coercivity of 1.72 kOe and moderate magnetization of 134 emu/cm 3 at a low current density of 5.5×10 6 A/cm 2 under an in-plane longitudinal magnetic field of ±3 kOe (Figure 15b).…”
Section: Bulk Sot Materialsmentioning
confidence: 99%
“…In conventional spin‐current generator/magnet (SCG/M) bilayers ( Figure a) the efficiency of the damping‐like spin–orbit torque (ξDLj$\xi _{DL}^j$) is usually low, particularly when θ SH is small and when T int is far less than unity due to spin memory loss [ 153–161 ] and spin backflow [ 149,162–166 ] (e.g., ξDLj$\xi _{DL}^j$ ≈ 0.05–0.15 for Pt/3 d ferromagnet [ 16 ] ). A more critical limitation of the bilayer scheme is that the efficiency of the damping‐like SOT per magnetic layer thickness ( t ), ξDLj$\xi _{DL}^j$/ t , is inversely proportional to t .…”
Section: Choice Of Perpendicular Magnetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to exchange bias in FM/AFM, the pseudo-exchange bias between two FMs is also an effective approach to introduce interface effective magnetic field [79,80]. Apart from this, structural asymmetry can introduce tilted PMA of the FM, effectively enabling all electrical deterministic SOT switching [81][82][83][84].…”
Section: All Electrical Sot Control Enabled By Magnetization Engineeringmentioning
confidence: 99%
“…Recently, the novel bulk SOT (BSOT) effect has attracted intensive research interest because it can break through the interfacial nature of conventional SOT in NM/FM bilayer structures, and simultaneously implement high Δ and low J c . [16][17][18][19][20][21] The BSOTinduced magnetization switching has been demonstrated in single magnetic layers, such as GaMnAs with globally or locally broken inversion symmetry. But it is detrimental to practical applications due to the requirement of low temperature.…”
Section: Introductionmentioning
confidence: 99%